Factors associated with cutaneous ulcers among children in two yaws-endemic districts in Ghana - Rafiq Nii Attoh Okine; Bismark Sarfo; Richard M. Adanu; Cynthia Kwakye-Maclean; Francis Adjei Osei (BMC, 2020)
Abstract Background Yaws is a chronic relapsing disease caused by Treponema pallidum subspecies pertunue, which can result in severe disability and deformities. Children below the age of 15 years in resource-poor communities are the most affected. Several non-specific factors facilitate the continuous transmission and resurgence of the disease. Endemic communities in rural Ghana continue to report cases despite the roll out of several intervention strategies in the past years. The objective of this study was to determine the factors associated with cutaneous ulcers among children in two yaws-endemic districts in Ghana. Methods A community-based unmatched 1:2 case-control study was conducted among children between 1 and 15 years. Data on socio-demographic, environmental and behavioral factors were collected using a structured questionnaire. Active case search and confirmation was done using the Dual Path Platform (DPP) Syphilis Screen and Confirm test kit. Data were analyzed using STATA 15. Logistic regression was done to determine the exposures that were associated with yaws infection at 0.05 significant level. Results Sixty-two cases and 124 controls were recruited for the study. The adjusted multivariable logistic regression model showed that yaws infection was more likely among individuals who reside in overcrowded compound houses (aOR = 25.42, 95% CI: 6.15-105.09) and with poor handwashing habits (aOR = 6.46, 95% CI: 1.89-22.04). Male (aOR = 4.15, 95% CI: 1.29-13.36) and increasing age (aOR = 5.90, 95% CI: 1.97-17.67) were also associated with yaws infection. Conclusions Poor personal hygiene, overcrowding and lack of access to improved sanitary facilities are the factors that facilitate the transmission of yaws in the Awutu Senya West and Upper West Akyem districts. Yaws was also more common among males and school-aged children. Improving living conditions, access to good sanitary facilities and encouraging good personal hygiene practices should be core features of eradication programs in endemic communities.